Adolescents' gender stereotypes, differences and other aspects of behaviour in the Eastern Cape Province, South Africa. - Mwamwenda, Tuntufye (My University, 2013)
While in metropolitan countries gender stereotypes has been a topic of extensive research, this has not been the case in African countries including South Africa. Such a deficit served as a motivation for investigating the extent to which gender stereotypes among adolescents prevail in the Eastern Cape Province of South Africa. The sample was based on 599 Junior Secondary School students in grades 7-9 in Mthatha Eastern Province, South Africa. A questionnaire on gender stereotypes consisting of ten statements was administered to 239 girls and 360 boys drawn from five Junior Secondary Schools participating in the study. A chi square was used for statistical analysis. Based on the entire sample, the responses for each one of the ten statements in the questionnaire, early adolescents scored statistically significant on gender stereotypes. Further analysis based on gender showed statistically significant differences in gender stereotypes. The findings confirmed the findings of researchers in gender stereotypes in metropolitan countries. As reported in the literature, South African early adolescents experience gender stereotypes as observed in other cultures. Such results have implications for children, parents, teachers, educational institutions and society at large.
Keywords: Stereotypes, adolescents, gender.